Pengaruh Citra Merek dan Harga terhadap Keputusan Pembelian Sepeda Motor Matic Honda Scoopy (Survei Pada Konsumen Sepeda Motor Matic Honda Scoopy di PD. Lima Motor Cilamaya-Karawang) - Vira Rizky Septiani; Odang Kusmayadi (Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine and analyze the relationship between Brand Image and Product Price Honda Sccopy, to determine the partial influence on purchasing decisions, to determine and analyze costs on purchasing decisions Honda Sccopy bicycle products. To determine the simultaneous effect of Brand Image and Cost on the purchase of Honda Sccopy motorcycle products at PD. Five Cilamaya Machines. The technique in this test uses quantitative methods with descriptive and verification approaches. The sample used was 195 samples with a non-probability sampling technique using a Likert scale procedure and path analysis. The results of this study are brand image and cost have a relationship of 0.618 or 61.8%. There is a partial effect of brand image on purchasing decisions by 30.1% and price on purchasing decisions by 31.5%. There is a simultaneous influence between brand image, price on purchasing decisions of 61.6% while the remaining 38.4% are different factors that are not analyzed.